Analisis Pengaruh Harga dan Lokasi terhadap Keputusan Pembelian pada Toko Nirwana di Kabupaten Mamuju - Kasita, Syukrina Dwi; Aqil, Muhammad; Sibgatullah, Muhammad; Adra, Sri (Jurnal Bisnis, Manajemen, dan Akuntansi, 2024)
The aim of this research is to determine the influence of price on purchasing decisions at the Nirwana Store in Mamuju Regency, the influence of location on purchasing decisions at the Nirwana Store in Mamuju Regency, the influence of price and location simultaneously on purchasing decisions at the Nirwana Store in Mamuju Regency.This type of research is quantitative with primary data taken using a questionnaire. The respondent population is Nirwana Store consumers. Samples were taken using proportional random sampling technique. The number of samples used was 50 people. Data from the questionnaire was analyzed using multiple linear regression techniques and t tests and F tests using SPSS tools. The results of this research show that the price variable has no partial effect on purchasing decisions and the location variable has a partial effect on purchasing decisions at the Nirwana Store. The results of the F test show that the price and location variables influence simultaneously (simultaneously) on purchasing decisions at the Nirwana Store. From the results of the analysis, suggestions can be made that Nirwana Stores should be able to use more pricing strategies to increase purchasing productivity.Originality of this research lies in the fact that research has never been conducted on Nirwana Shop Consumers in Mamuju Regency.